Las emociones en la entrevista en psicooncología - Modolell, Elisabet; Casado, Susana; Sanz, Jaime (Psicooncología, 2004)
In the present article we expose a model for a first psychological interview with cancer patients. We set our basis on the integration of the psychologist on the Oncology teams. We refer the importance of communication. Communication is the central element of the therapeutic relationship. The meeting ought to be warm and empathic. We detach the presence of both patient and care-givers emotions. Psychologists should be experts managing their own emotions, the patient and his family’s emotions and the sanitary team emotions. The first interview objective is as simple as getting to know the patient and to establish a profitable link. We aim to reach a mutual confidence to allow an assistance relationship. Two key moments that we shall not neglect are greeting and farewell. The information we manage to get includes socio demographic data, illness news and the illness patient narration. In the psycho-oncologist exploration we examine the symptoms area, behaviour, emotions, cognitions, spiritual beliefs and socio familiar support. The most important thing in a first psycho-oncologist interview is listening, connecting with the patient and come to an agreement to reach the objectives